Sistem Monitoring Hidroponik Pada Tanaman Pakcoy Dengan Metode Nutrient Film Technique (Nft) Berbasis Internet Of Things - Huda, Zikril; Marindani, Elang Derdian; Wibowo Sanjaya , Bomo (Ridwan Institute, 2025)
This research develops and implements an Internet of Things (IoT)-based hydroponic system designed to automatically monitor and control nutrient quality to ensure optimal plant growth. The system is capable of monitoring crucial parameters such as pH, Total Dissolved Solids (TDS), water temperature, ambient temperature, and ambient humidity, and possesses the capability to control pH and TDS levels in the nutrient solution. The implementation was conducted on pakcoy cultivation using the Nutrient Film Technique (NFT) hydroponic method, chosen for its suitability with IoT integration. The platform utilized is a website connected to a Firebase Database, where sensor data is processed by a microcontroller and transmitted to the database for real-time display. Testing results indicate sensor error percentages of 1.53% for water temperature, 6.31% for pH, 9.17% for TDS, 2.17% for ambient temperature, and 1.25% for ambient humidity. Overall, the sensor readings used in this system demonstrate satisfactory performance in measuring water quality and environmental parameters, thereby effectively supporting plant quality maintenance.